Improving the Loyalty of Customer through the Effectiveness of Customer Satisfaction, Service Quality, and Food Quality - Cahaya, Yohanes Ferry; Winarti, Ch. Endah; Erasashanti, Annathasia Puji (Dinasti Publisher, 2023)
The food industry is one of the business sectors that is future-oriented, as evidenced by food being one of the basic needs of the community. Therefore, it is necessary to examine customer loyalty in the food industry through the role of customer satisfaction, service quality and food quality, as in this study. In developing this research, quantitative descriptive methods were used by involving a sample of 100 respondents to obtain analysis data, which was then processed and analyzed using SEM-PLS. The research reveals that there is a significant positive correlation occurred of service quality along to food quality which affecting customer satisfaction. And this customer satisfaction also affects in increasing customer loyalty to Subway Indonesia. These results indicates that Subway Indonesia needs to maintain their improvement on service quality and food quality which served based on consumers expectations, so as to increase customer satisfaction and loyalty.